Dampak Sistem Blok Terhadap Kemampuan Mahasiswa Pendidikan IPA Tahun 2025 Dalam Mengatur Waktu dan Menyelesaikan Tugas Akademik Serta Laporan Praktikum: (The Impact of the Block System on the Ability of Science Education Students in 2025 to Manage Time and Complete Academic Assignments and Practical Reports) - Gandi Purba, Sonia; Novitasari, Pera; Sibarani, Ruth Masta Yemima; Sihombing , Windry Sari; Nika, Ayu (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to evaluate the impact of implementing a block system on the time management skills and academic task and practicum report completion of students in the Science Education program at UNIMED class of 2025. The research employed a quantitative approach with an ex-post facto design, involving 95 participants selected through total sampling. Data were collected using a Likert-scale questionnaire consisting of 15 statements. Descriptive analysis revealed that the block system positively influenced students’ learning concentration, as indicated by a high percentage of affirmative responses regarding time management and task completion. The mean score of 49.42 with a standard deviation of 5.13 demonstrated uniformity in respondents’ perceptions. However, students faced challenges such as heavy workloads, overlapping deadlines, and insufficient feedback from lecturers concerning practicum report preparation. Overall, the block system was deemed effective, yet improvements are necessary to ensure a more balanced learning process that adequately supports the students’ needs. Abstrak. Penelitian ini bertujuan untuk menganalisis dampak penerapan sistem blok terhadap kemampuan mahasiswa Pendidikan IPA UNIMED angkatan 2025 dalam mengatur waktu serta menyelesaikan tugas akademik dan laporan praktikum. Penelitian menggunakan pendekatan kuantitatif dengan desain ekspos-fakto dan melibatkan 95 mahasiswa sebagai responden melalui teknik total sampling. Data diperoleh dari angket skala Likert berisi 15 pernyataan yang mengukur aspek manajemen waktu dan penyelesaian tugas. Hasil analisis deskriptif menunjukkan bahwa sistem blok berkontribusi positif terhadap peningkatan fokus belajar dan keteraturan penyelesaian tugas, tercermin dari dominasi respons afirmatif serta nilai rata-rata 49,42 dengan standar deviasi 5,13 yang mengindikasikan konsistensi persepsi mahasiswa. Meskipun demikian, beban tugas yang padat, tenggat waktu yang tumpang tindih, dan kurang optimalnya umpan balik dosen menjadi kendala utama yang memengaruhi kualitas laporan praktikum. Secara keseluruhan, sistem blok dinilai efektif namun memerlukan penataan beban akademik dan peningkatan dukungan pedagogis agar implementasinya lebih optimal.